Application of Problem Posing Model for Achievement The Result of Physics Study at SMA Negeri 1 Taniwel - Amelia Niwele; Beatus M Laka (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2018)
The purpose of this study was to determine the achievement of student learning outcomes usingproblem posing model in SMA Negeri I Taniwel. This type of research was descriptive. Random samplingtechnique was conducted to determine the sample of research that is class XI IPA 1 SMA Negeri I Taniwel.Technique of data analysis in the form of analysis of student achievement test result based on referencebenchmark rating or reference standard. Formative test results (posttest) showed that most statements haveachieved higher scores, after getting treatment through the problem posing model applied. The resultsshowed that the problem posing model can help students in achieving good physics learning outcomes,especially on business and energy concepts with a final value of 82.6.